Enhanced N-type Semiconducting Performance of Asymmetric Monochlorinated Isoindigo-based Semiregioregular Polymers under Dynamic Forces - Kim, Younghyo; Hwang, Kyoungtae; Yang, Dongseong; Choi, Yeonsu; Kim, Yunseul; Moon, Yina; Park, Jong-Jin; Lee, Minwoo; Kim, Dong-Yu (American Chemical Society, 2024)
The asymmetric monochlorination strategy not only effectively addresses the steric issues in conventional dichlorination but also enables the development of promising acceptor units and semiregioregular polymers. Herein, monochlorinated isoindigo (1CIID) is successfully designed and synthesized by selectively introducing single chlorine (Cl) atoms. Furthermore, the 1CIID copolymerizes with two donor counterparts, centrosymmetric 2,2'-bithiophene (2T) and axisymmetric 4,7-di(thiophen-2-yl)benzo[1,2,5]thiadiazole (DTBT), forming two polymers, P1CIID-2T and P1CIID-DTBT. These polymers exhibit notable differences in backbone linearity and dipole moments, influenced by the symmetry of their donor counterparts. In particular, P1CIID-2T, which contains a centrosymmetric 2T unit, demonstrates a linear backbone and a significant dipole moment of 10.20 D. These properties contribute to the favorable film morphology of P1CIID-2T, characterized by highly ordered crystallinity in the presence of fifth-order (500) X-ray diffraction peaks. Notably, P1CIID-2T exhibits a significant improvement in molecular alignment under dynamic force, resulting in over 8-fold improvement in the performance of organic field-effect transistor (OFET) devices, with superior electron mobility up to 1.22 cm(2) V-1 s(-1). This study represents the first synthesis of asymmetric monochlorinated isoindigo-based conjugated polymers, highlighting the potential of asymmetric monochlorination for developing n-type semiconducting polymers. Moreover, our findings provide valuable insights into the relationship between the molecular structure and properties.